HUBUNGAN FAKTOR DEMOGRAFI DENGAN PENGETAHUAN CARA PENYIMPANAN DAN PEMBUANGAN OBAT KERAS DI KELURAHAN DUREN SAWIT JAKARTA TIMUR - Doni Iswandani; Guruh Subagya; Aries Meryta (Jurnal Farmasi IKIFA, 2024)
ABSTRACT Convenient Drug storage is to retard decomposition therefore all drugs should be stored inside the original package in a cool place away from moist, sun and bright. The aim of this research is to determine the relationship between demographic factors regarding knowledge the importance of convenient home drug storage and disposal in the community in Duren Sawit Village, East Jakarta. This research is non-experimental with a total of 269 respondents. Data was taken using a questionnaire with a total of 10 questions. The results of the research that has been done can be seen that the description of knowledge about drug storage who have good knowledge as many as 74 people (27%), who have moderate knowledge as many as 107 people (40%) and who have poor knowledge as many as 88 people (33%). The results of the research that has been done can be seen that the description of knowledge about drug disposal with good knowledge is 118 people (44%), who have moderate knowledge as many as 101 people (37%) and who have poor knowledge are 50 people (19%). Based on the results of the research, people's knowledge about the storage and disposal of drugs in Duren Sawit Village, East Jakarta is moderate as much as 120 out of 269 respondents (45%). Based on statistical calculations with the Spearman rho test, it shows that there is no relationship between age and the level of knowledge because the sig value (0.68) > 0.05.